2019
DOI: 10.1055/a-0983-1265
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Scoliosis Correction as Alternative Treatment for Patients with Adolescent Idiopathic Scoliosis: a Non-Fusion Surgical Technique

Abstract: Anterior dynamic scoliosis correction is an innovative non-fusion option in the treatment of patients with severe adolescent scoliosis. Growth modulation and sometimes intraoperative curve correction is achieved by convex insertion of segmental screws and a flexible polyethylene cord. The present review analyses and discusses the current literature and proposes a new treatment algorithm that is based on our own experience. Short term results are published for approximately 100 patients from different instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
0
14
0
2
Order By: Relevance
“…The following radiologic parameters were measured before surgery, at the 1st standing X-ray and at the 1-year follow-up: Cobb angle, coronal balance (CB, the linear distance between C7 plumb line and the central sacral vertical line), pelvic incidence (PI), pelvic tilt (PT), thoracic kyphosis (TK), lumbar lordosis (LL) and sagittal vertical alignment (SVA). Curve type was determined according to our previously published classification [11]. This classification is based on the potential advantages and feasibility of VBT over fusion: lumbar curves are defined as type 1, double curves type 2, long thoracic curves with L2 being the first caudal that touches the central sacral vertical line (CSVL) are type 3, short thoracic curves with L1 or higher touching the CSVL are described as type 4 and rigid proximal thoracic curves as type 5.…”
Section: Methodsmentioning
confidence: 99%
“…The following radiologic parameters were measured before surgery, at the 1st standing X-ray and at the 1-year follow-up: Cobb angle, coronal balance (CB, the linear distance between C7 plumb line and the central sacral vertical line), pelvic incidence (PI), pelvic tilt (PT), thoracic kyphosis (TK), lumbar lordosis (LL) and sagittal vertical alignment (SVA). Curve type was determined according to our previously published classification [11]. This classification is based on the potential advantages and feasibility of VBT over fusion: lumbar curves are defined as type 1, double curves type 2, long thoracic curves with L2 being the first caudal that touches the central sacral vertical line (CSVL) are type 3, short thoracic curves with L1 or higher touching the CSVL are described as type 4 and rigid proximal thoracic curves as type 5.…”
Section: Methodsmentioning
confidence: 99%
“…For patients requiring a bilateral correction, this was conducted in one stage with lumbar instrumentation performed first, as the authors feel instrumentation of the lumbar curve is mentally and physically more demanding. After suturing and dressing the wounds, patients were repositioned for thoracic instrumentation [2,3]. The screws were placed bicortically following anatomic landmarks and under antero-posterior fluoroscopic control.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…However, these patients were not included in this work. While research aimed to identify the ideal candidate for VBT is still ongoing, the authors developed a classification based on the benefits of VBT over fusion and on the magnitude and flexibility of the curve [2] (Table 1). This classification is employed for immature patients (Risser ≤ 4 and/or Sanders ≤ 7) with curves between 40° and 70°.…”
Section: Patient Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, the Food and Drug Administration (FDA) has approved the first device for US patients, whereas another device has already received CE approval (European approval) in 2017. Several basic sciences as well as clinical studies have confirmed safety and efficacy, including a prospective Humanitarian Device Exemption (HDE) study that was controlled by the FDA [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%